Fuzzy-based adaptive length burst assembly technique for loss reduction in optical burst switched networks - Abubakar, Muhammad Umaru (American Scientific Publishers, 2016)
Optical burst switching (OBS) is a type of optical switching technology that harnesses the enormous bandwidth potential of the optical fiber to transport huge amounts of data in the form of jumbo packets which are mainly known as bursts. An important issue in OBS is high burst loss resulting from high number of burst contentions. In order to address this issue, an intelligent burst assembly algorithm named Fuzzy-based Adaptive Length Burst Assembly (FALBA) algorithm is proposed. FALBA uses fuzzy logic to intelligently adjust the burst assembly parameter using the incoming traffic load and the current burst size parameter. Simulation results have shown that FALBA out performs the fuzzy adaptive threshold algorithm in terms of burst loss ratio.